Evaluation of the properties of hybrid yellow poplar (Liriodendron sino-americanum): A comparison study with yellow poplar (Liriodendron tulipifera) - Feng, Xinhao; Sheng, Yating; Ge, Xiaowei; Wu, Zhihui; Huang, Qiongtao (Maderas. Ciencia y Tecnología, 2021)
As one of fast-growth wood species, hybrid yellow poplar (YP-h, Liriodendron sino-americanum) has been extensively planted throughout of China, however, little is known about its properties and applicability in structural and nonstructural applications such as construction and furniture. The aim of this study was to evaluate the properties of YP-h and examine its differences with yellow poplar (YP, Liriodendron tulipifera). The average vessel diameter of YP-h (55 μm) was 19 % lower than YP (68 μm), but, the density of YP-h was 37 % higher than YP and the dimensional change in YP-h was higher than YP. Comparable tensile strength and flexural modulus were found in YP-h and YP, however, the flexural, shear, and impact strength of YP-h was 35 %, 40 %, and 55 % higher than those of YP, respectively. The drilling, mortising, and turning processability of YP-h were superior to those of YP. Compared to the gluing and coating performance of YP, YP-h had inferior gluing properties and equivalent coating performance. Therefore, hybrid yellow poplar can be an ideal candidate for yellow poplar to be utilized in construction and furniture.